1961
DOI: 10.1029/jz066i001p00067
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of electron densities in the exosphere by means of nose whistlers

Abstract: The nose whistler dispersion equation was numerically integrated using the following assumed functions for the electron density distribution: (1)N=K (2) N = KR−3. (3) N = KR−3 exp(3.03/R). N is the electron number density, R is the distance from the earth's center, and K a constant of proportionality. Several whistlers that were received at College on March 19, 1959, were analyzed to obtain electron densities. Each of these whistlers consists of a number of branches having successively lower nose frequencies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1961
1961
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…The neutral hydrogen distribution in the exosphere has been determined by Opik and Singer [1961], the relative distribution being calculated from theory, the normalization being The model which we adopt for the purpose of calculating trapped particle intensities is obtained from these sources and is shown in Table 1. The effective densities as defined in Appendix I are shown in Figure 4 and compared with results of Allcock [1959] and Pope [1961], together with a theoretical distribution calculated by Johnson [1960]. It should be pointed out explicitly that we are neglecting the rather large time variations which certainly exist for all of the components.…”
Section: Equilibrium Distribution Of Electronsmentioning
confidence: 99%
“…The neutral hydrogen distribution in the exosphere has been determined by Opik and Singer [1961], the relative distribution being calculated from theory, the normalization being The model which we adopt for the purpose of calculating trapped particle intensities is obtained from these sources and is shown in Table 1. The effective densities as defined in Appendix I are shown in Figure 4 and compared with results of Allcock [1959] and Pope [1961], together with a theoretical distribution calculated by Johnson [1960]. It should be pointed out explicitly that we are neglecting the rather large time variations which certainly exist for all of the components.…”
Section: Equilibrium Distribution Of Electronsmentioning
confidence: 99%
“…">IntroductionBy mass, the magnetosphere is dominated by plasma with energies below 100 eV. Beginning with the earliest ground-based whistler [Storey, 1953;Pope, 1961;Smith, 1961 ] and spacecraft [Gringauz et al, 1960a, b] observations, these core plasmas have been studied for many years. Plasma wave frequencies, particle heating, and instability growth rates can be strongly influenced by the presence and concentrations of core plasmas.…”
mentioning
confidence: 99%
“…Chapman and Ferraro [1931] demonstrated that these changes can be produced when a highly ionized corpuseular stream is propagated from the sun across the empty space between the sun and earth, and pushes inward on the geomagnetic field. Modifications of their theory were presented later, since it was found that a highly conductive eorpuseular stream is flowing out continuously from the sun [Bierman, 1957] and that the space inside the geomagnetic field is filled with sufficient plasma to be a good electrical conductor [Storey, 1953;and Pope, 1961]. It is now considered that, the geomagnetic field is always confined to a region of finite dimensions under the influence of a continuously flowing eorpuscular stream [Dungey, 1954;Hoyle, 1956;Parker, 1958;Obayashi, 1958;and Beard, 1960].…”
mentioning
confidence: 99%